Acceleration of recovery of gastric epithelial integrity by 16,16-dimethyl prostaglandin E2. - Wallace, J. L. (1985)
The effects of pretreatment with 16,16-dimethyl prostaglandin E2 (DmPGE2) on the recovery of gastric mucosal 'barrier' parameters after ethanol-induced damage were studied using an ex vivo chamber preparation in the rat. DmPGE2 (4-40 micrograms kg-1) significantly reduced the extent of haemorrhagic damage to the gastric mucosa induced by the topical application of 50% ethanol followed by 0.05 M hydrochloric acid. The lowest dose of DmPGE2 tested (4 micrograms kg-1) had no effect on the ethanol-induced changes in transmucosal potential difference (PD) or K+ efflux. However, DmPGE2 at doses at 20 or 40 micrograms kg-1 significantly reduced the changes in these indices of epithelial integrity. The recovery of PD and K+ efflux to control levels after ethanol-injury was accelerated by DmPGE2. With the two higher doses of DmPGE2 (20 and 40 micrograms kg-1) there was a significantly (P less than 0.001) lower level of epithelial discontinuity, measured histologically, in samples taken at the end of the experiment. These results suggest that at the higher doses, DmPGE2 confers some protection to the gastric epithelium as well as accelerating the recovery of epithelial integrity after damage induced by ethanol.